PCS-9 Effect of Freeze Drying of Follicular Fluid from Waste of Aceh Cattle Ovary on the Estradiol Concentration - M Adam; G Gholib; M Hamdan; M Syafruddin; Hafizuddin Hafizuddin; H Alief (Hemera Zoa, 2018)
Aceh cattle are one of the many cow’s species that are widely preserved and distributed in Aceh Province. This species is the result of a cross between Bos sundaicus and Bos indicus and has been designated as a native Indonesian class of cattle in 2011 by the Minister of Agriculture of Indonesia through the decision of the Minister of Agriculture number 2907 / Kpts / OT.140 / 6/2011 [1]. Aceh's cattle population in 2017 in total was 627,629 species [2]. Slaughtering the cows results in the obtaining of byproduct or waste such as ovaries. The ovarium of female cows is one of the complement results of animal slaughter house which is infrequently used. In fact, the ovaries comprise follicles which contain many active compounds inside the follicular fluids such as insulin-like growth factor I (IGF-I), follicle stimulating hormone (FSH), luteinizing hormone (LH), estrogen and progesterone [3]. Freeze drying/lyophilization is one of the preservative process which are generally used in food and non-food processing. This study was conducted to determine the effect of these methods on the concentration of estrogen in follicular fluid.